(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2026)
This study aimed to identify the impact of applying governance principles on the performance of civil society organizations (CSOs) in the Republic of Yemen by analyzing the relationship between governance principles, namely (transparency, accountability, fairness, participation, and the rule of law), and CSO performance, which was measured through the dimensions of efficiency and effectiveness. The study adopted a descriptive-analytical approach and utilized a questionnaire as the primary data collection instrument. A total of 116 questionnaires were distributed to senior and middle-level administrative leaders, including organization presidents, board members, secretaries-general, executive directors, department heads and managers, as well as program and project managers across 27 civil society organizations operating in Yemen. Data were analyzed using the Statistical Package for the Social Sciences (SPSS). The findings revealed a positive and statistically significant impact of governance principles (transparency, accountability, participation, fairness, and the rule of law) on the performance of civil society organizations in Yemen. Among these dimensions, participation exerted the strongest influence on organizational performance, whereas transparency demonstrated the weakest influence. The results also indicated that both the level of governance practice and the level of organizational performance among Yemeni civil society organizations were high. Based on these findings, the study proposed several recommendations, most notably the need to further strengthen the implementation of governance principles within civil society organizations in Yemen, given their critical role in directing resources and capabilities toward achieving organizational objectives and ensuring organizational sustainability through greater efficiency and effectiveness.